Yachnik L. M. The peculiarities of Alexander Kushner reception of the Russian poetic classics - Yachnik L. M. (Philological Treatises, 2020)
The article deals with the most common features of Alexander Kushner reception of classical age Russian poetry. The main attention is paid to the forms of presenting the Russian poetry in Kushner verses. The using of inverted interpretation and different types of allusion has been examined too.